Seed dispersal networks in tropical forest fragments: Area effects, remnant species, and interaction diversity. (16th December 2019) - Emer, Carine; Jordano, Pedro; Pizo, Marco A.; Ribeiro, Milton C.; da Silva, Fernanda R.; Galetti, Mauro
Abstract: Seed dispersal interactions involve key ecological processes in tropical forests that help to maintain ecosystem functioning. Yet this functionality may be threatened by increasing habitat loss, defaunation, and fragmentation. However, generalist species, and their interactions, can benefit from the habitat change caused by human disturbance while more specialized interactions mostly disappear. Therefore, changes in the structure of the local, within fragment, networks can be expected. Here we investigated how the structure of seed dispersal networks changes along a gradient of increasing habitat fragmentation. We analyzed 16 bird seed dispersal assemblages from forest fragments of a biodiversity‐rich ecosystem. We found significant species–, interaction–, and network–area relationships, yet the later was determined by the number of species remaining in each community. The number of frugivorous bird and plant species, their interactions, and the number of links per species decreases as area is lost in the fragmented landscape. In contrast, network nestedness has a negative relationship with fragment area, suggesting an increasing generalization of the network structure in the gradient of fragmentation. Network specialization was not significantly affected by area, indicating that some network properties may be invariant to disturbance. Still, the local extinction of partner species, paralleled by a loss of interactions and specialist–specialist bird–plant seed dispersal associations, suggests the functional homogenization of the system as area is lost. Our study provides empirical evidence for network–area relationships driven by the presence/absence of remnant species and the interactions they perform. Abstract in Spanish is available with online material. RESUMO: Interações de dispersão de sementes formam um processo ecológico chave em florestas tropicais onde colaboram na manutenção do funcionamento do ecossistema. Porém, esta funcionalidade pode estar ameaçada pelo aumento na perda e fragmentação do habitat. Enquanto espécies generalistas e suas interações podem se beneficiar da mudança de habitat causada por distúrbios antrópicos, interações envolvendo espécies mais especialistas são, na maioria, eliminadas. Desta forma, mudanças nas redes locais, dentro de fragmentos florestais, são esperadas. Neste trabalho nós investigamos como a estrutura de redes de dispersão de sementes mudam em um gradiente de fragmentação do habitat. Nós analisamos 16 comunidades de dispersão de sementes espacialmente explícitas e distribuídas em fragmentos florestais de um ecossistema rico em biodiversidade. Nós encontramos relações significativas entre a área do fragmento e espécies, interações e estrutura das redes, sendo que o último foi determinado pelo número de espécies remanescentes em cada comunidade. O número de espécies de aves frugívoras e plantas e as interações entre eles, bem como o número de links por espécie diminuíram significativamente conforme a área dos fragmentos é perdida. Por outro lado, o aninhamento da rede mostrou uma relação negativa com a área do fragmento, sugerindo um aumento da generalização da estrutura das redes com a fragmentação do habitat. No entanto, o grau de especialização das redes não foi afetado pela área, indicando que algumas propriedades de rede podem ser resistentes à perturbação. Sendo assim, a extinção local de espécies parceiras, conjuntamente com a perda das interações e associações planta‐dispersor mais especializadas, sugere uma homogeneização do sistema conforme a área do fragmento é perdida. Nosso estudo fornece evidências empíricas para as relações rede‐área, sendo estas direcionadas pela presença e/ou ausência das espécies remanescentes bem como das interações que estas realizam.